Deferred Tax Expense, Sales Growth, Capital Intensity, Transfer Pricing and Tax Avoidance - Apriliani, Shanda; Hidayati, Wahyu Nurul (Universitas Pamulang, 2023)
This study aims to examine the effect of deferred tax expense, sales growth, capital intensity, and transfer pricing on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange from 2016-2022. This method of research is quantitative research. The number of samples used in this study amounted to 49 companies from 7 companies in the energy sector, obtained using purposive sampling based on predetermined criteria. The data is secondary data, which audited financial statements for the 2016-2022 period obtained through the official website of the Indonesia Stock Exchange. The data analysis techniques used are descriptive statistics and panel data regression analysis using the Eviews 9 application software. The resulting study reveals that deferred tax expense partially affects tax avoidance, sales growth partially affects tax avoidance, capital intensity partially does not, and transfer pricing partially does not affect tax avoidance. Meanwhile, deferred tax expense, sales growth, capital intensity, and transfer pricing simultaneously affect tax avoidance.